Entanglement distribution between two separate systems via a third system - Krisnanda, I Wayan Gede Tanjung (2015)
Entanglement is a quantum correlation between pairs (or groups) of systems. It is a resource of crucial importance for quantum information processing such as quantum cryptography and quantum computing. In this thesis, we investigated entanglement distribution between two separate systems A and B using a third system C as an ancilla. For the case where C is allowed to interact discretely with A and then B, we found entanglement inequality: E(A-BC)-E(B-AC)<= E(C-AB) in pure states. We also found violations of such inequality that will lead to excessive distribution in which entanglement distributed is higher than entanglement communicated. For the case where C is allowed to interact continuously with A and B, we proved that entanglement in the partition A-B cannot increase under the condition that the state of the whole system is pure and the state of C is separable from AB. If the system evolves under the Born approximation, entanglement also cannot grow. This suggests that correlation in the partition C-AB is needed to distribute entanglement. In pure states, we computed entanglement as a function of time with perturbation theory. We observed an artefact that entanglement gain is possible with separable C. We also computed entanglement in weak and strong interaction limit. In weak interaction, we found that maximum entanglement is achieved at the same time for weaker interaction strength at the expense of its value. However, in strong interaction the same value of maximum entanglement can be achieved for weaker interaction strength at the expense of time.